INTERPOLATION OF RASTER SURFACES (GRID INTERPOLATION).THE KRIGING METHOD: INTERPOLATION OF RASTER SURFACES (GRID INTERPOLATION).THE KRIGING METHOD - Ivanov, Sabin (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
Interpolation is a process that determines the unknown z-values of pixels in raster (GRID) form, of a system of points, or in vector (TIN) form of a limited number of points with known data about them. It is used to determine the unknown values at any geographical point of: altitude, precipitation, chemical concentrations, noise level, etc.